2020
DOI: 10.1097/md.0000000000022275
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of electroacupuncture against urinary incontinence after stroke

Abstract: Background: Urinary incontinence (UI) is still a persistent challenge in many stroke survivors, affecting the quality of life and emotional being of these individuals. Numerous studies have demonstrated the curative effect of electroacupuncture on post-stroke incontinence, however they were mired with questionable quality and inconsistencies in safety and efficacy. Therefore, the main objective of this meta-analysis is to provide a comprehensive evaluation of the efficacy and safety of electroacup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…UI is still a challenge for many stroke survivors and affects their quality of life [ 3 ]. Several studies have reported that post-stroke UI affects the quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…UI is still a challenge for many stroke survivors and affects their quality of life [ 3 ]. Several studies have reported that post-stroke UI affects the quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral medication of detrusor overactivity is associated with several complications such as cognitive damage and dry mouth [3,14]. The effectiveness of behaviour training, acupuncture, and pelvic floor muscle exercises remains unclear [1,7,[15][16][17]. Therefore, further investigation is needed to establish an effective therapy for PSI patients with DO.…”
Section: Introductionmentioning
confidence: 99%